An overview of medication adherence: Measurement methods and interventions - Miceva Dijana; Smilkov Katarina; Gjorgieva Ackova Darinka; Naumovska Zorica; Lazarova Biljana; Angelovska Bistra; Drakalska Sersemova Elena (Arhiv za farmaciju, 2025)
Medication adherence is essential for achieving therapeutic outcomes. However, many patients do not follow their prescribed medication regimens. About 50% of patients do not adhere to their pharmacotherapy, making medication adherence a widespread issue. Accurately measuring adherence is essential for effective care planning and intervention. This paper reviews various methods for measuring medication adherence, highlighting the advantages and disadvantages of each approach. Many factors can affect medication adherence. This review focuses on practical ways to measure adherence and strategies to enhance it, underscoring its importance in achieving better healthcare results. Healthcare providers must prioritize medication adherence, as it directly impacts the effectiveness of treatment and overall public health outcomes.